Oral manifestations of histiocytosis of langerhans cells : a pediatric case involving mandible bone = Manifestaciones orales de histiocitosis de células de Langerhans : un caso pediátrico relacionado con el hueso mandibular - Montero Sánchez, René Abdiel
Langerhans cells histiocytosis is a rare disease characterized by monoclonal proliferation and migration of special dendritic cells in a variety of organs, most commonly appears eosinophilic granuloma localized, often solitary, and bone lesions that occurs predominantly in pediatric patients. Although is most prevalent in children under the age of 15, this disorder presents in all ages and occurs at a rate of 2 to 5 cases per million per year. LCH is a complex entity; the clinic manifestations can mimic other common conditions and therefore a comprehensive evaluation is indicated. Since oral manifestations are frequent, the early diagnose of this pathology could be detected by dental professionals. The aim of this case report is to describe a case of LCH who initially was misdiagnosed and treated for a dental infection. This disease requires accurate histopathological diagnosis and timely treatment; hence it is necessary to raise awareness among dentists to avoid misdiagnose of oral manifestations of LCH.